Pembentukan Peraturan Negeri yang Partisipatif Dalam Pelaksanaan Pemerintah Negeri Hutumuri Kecamatan Leitimur Selatan Kota Ambon - Eric Stenly Holle; Reny Heronia Nendissa; Junior A N Lumintang (AIWADTHU: Jurnal Pengabdian Hukum, 2021)
Introduction: Community involvement in the formation of Negeri Regulations from the beginning of the process to evaluation is a condition that must even exist in a country that adheres to the understanding of people's sovereignty.Purposes of Devotion: Providing education and legal knowledge to the Negeri Government and Public Affairs Hutumuri District of Leitimur South Ambon City so as to engage and be involved in every process of establishing the Regulation of Foreign. Method of Devotion: Sources describe materials related to the establishment of rules of domestic participatory followed by a discussion and question and answer between the presenters and participants in the activity.Results of the Devotion: The Negeri Government and the community are able to understand matters related to the formation of Negeri Regulations and are able to resolve problems related to community involvement in the process of forming Negeri Regulations as regulated in various laws and regulations so that it is hoped that the draft of a legal product in the form of a Negeri Regulation can actively involve the community in contributing thoughts, ideas, ideas, and suggestions that affect the substance of the Negeri Regulation